2019
DOI: 10.1177/1046496419876342
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating Violence Against First Responder Teams: Results and Ideas From the Hackmanathon

Abstract: First responders are on the front line of patient care and service, but research has shown that they are also on the front line of exposure to violence. Currently, there is a lack of evidence-based interventions that prepare first responders to handle violence on the job. With the increase in emergency medical services (EMS) call volume and reports of at least 57% of the EMS responders having experienced workplace violence, there is a need to develop scientifically systematic solutions to improve emergency res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(24 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Minimizing the risk when responding to violence is essential in addressing safety concerns and reducing workplace violence in the prehospital environment. Previous research has reported similar findings on the topics of minimizing risk, co‐attendance (police and paramedics), scene safety, engaging in violence prevention training, development and instigation of violence intervention programs, and situational awareness (Allen et al, 2019; Murray et al, 2019). In addition, the importance has been pointed out of knowing and identifying behavioral cues (agitation, aggressive outbursts, intimidation, and breaking furniture), which may be precursors to violence and need to be managed early to prevent potentially unsafe situations (Spencer et al, 2018; Usher et al, 2017).…”
Section: Discussionsupporting
confidence: 55%
“…Minimizing the risk when responding to violence is essential in addressing safety concerns and reducing workplace violence in the prehospital environment. Previous research has reported similar findings on the topics of minimizing risk, co‐attendance (police and paramedics), scene safety, engaging in violence prevention training, development and instigation of violence intervention programs, and situational awareness (Allen et al, 2019; Murray et al, 2019). In addition, the importance has been pointed out of knowing and identifying behavioral cues (agitation, aggressive outbursts, intimidation, and breaking furniture), which may be precursors to violence and need to be managed early to prevent potentially unsafe situations (Spencer et al, 2018; Usher et al, 2017).…”
Section: Discussionsupporting
confidence: 55%
“…We retrieved 127 publications from additional searches (ie, citation searching and the complementary open call), with a further 11 publications included in this review. In total, we included 42 studies in this review,7 8 18–57 with 39 studies (93%) focusing on developing social innovations 7 8 18–20 22–42 44–53 55–57. The PRISMA flowchart is presented in online supplemental figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 41 studies (98%) reported the number of designathon participants 7 8 18–53 55–57. The median number of individuals participating in designathons was 49 (IQR 34–90, range 6–434), and the median number of teams was 8 (IQR 5–14.5, range 2–40).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations